2021
DOI: 10.1097/bot.0000000000002183
|View full text |Cite
|
Sign up to set email alerts
|

Application of Negative Pressure Wound Therapy

Abstract: The video depicts the materials and steps for applying negative pressure wound therapy. The clinical case involves a patient who had sustained a thigh Morel-Lavallee lesion that developed overlying skin necrosis and drainage that was treated with surgical debridement and the application of negative pressure wound therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…After negative pressure sealing, negative pressure in the wound may remain unobstructed for a long time to ensure the drainage effect. Negative pressure reduces infection, cleans the environment and controls the pressure in the skin graft area, all of which are conducive to the survival of avulsed skin (24). In the present case, the degloved skin completely survived after negative pressure drainage and the granulation tissue of the skin defect wound grew well, which created conditions optimal for skin-flap transplantation.…”
Section: Date Proceduresmentioning
confidence: 51%
See 1 more Smart Citation
“…After negative pressure sealing, negative pressure in the wound may remain unobstructed for a long time to ensure the drainage effect. Negative pressure reduces infection, cleans the environment and controls the pressure in the skin graft area, all of which are conducive to the survival of avulsed skin (24). In the present case, the degloved skin completely survived after negative pressure drainage and the granulation tissue of the skin defect wound grew well, which created conditions optimal for skin-flap transplantation.…”
Section: Date Proceduresmentioning
confidence: 51%
“…The dressing was changed and a vacuum sealing drainage device was placed on first operation) the wound. Sep 2020 (24 right radius with a plate and the right radioulnar joint with screws. Jan 2021 (13 days after the last After the wound had healed, all sutures were removed.…”
Section: Date Proceduresmentioning
confidence: 99%
“…Although many studies have reported the efficacy of various treatment regimens, such as conservative treatment, percutaneous aspiration, sclerotherapy, minimally invasive surgery, open surgery, or negative pressure wound therapy (NPWT), high-quality evidence remains lacking. [5,[7][8][9][10] To the best of our knowledge, the number of cases of MLL treated with portable NPWT is very small and no reviews have been reported.…”
Section: Introductionmentioning
confidence: 99%